2019
DOI: 10.1111/1751-2980.12756
|View full text |Cite
|
Sign up to set email alerts
|

Relief of irritable bowel syndrome by fecal microbiota transplantation is associated with changes in diversity and composition of the gut microbiota

Abstract: Objective To evaluate the efficacy and safety of fecal microbiota transplantation (FMT) for refractory irritable bowel syndrome (IBS). Methods Microbiota suspensions from feces of the donors were injected into the intestines of 30 Chinese patients with refractory IBS. Microbiota composition analysis and genomic DNA extraction of fecal samples obtained from these patients at baseline and 1 month after FMT were performed. Clinical efficacy and safety of FMT were assessed using questionnaires covering four aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…Huang et al reported that FMT improved gastrointestinal symptoms and alleviated depression and anxiety in irritable bowel syndrome (IBS) patients. Further, gut microbiota analyses revealed that Methanobrevibacter and A. muciniphila were the most abundant fecal microbiota a month after compared to before FMT (88).…”
Section: Strategies To Increase the Abundance Of A Muciniphilamentioning
confidence: 96%
“…Huang et al reported that FMT improved gastrointestinal symptoms and alleviated depression and anxiety in irritable bowel syndrome (IBS) patients. Further, gut microbiota analyses revealed that Methanobrevibacter and A. muciniphila were the most abundant fecal microbiota a month after compared to before FMT (88).…”
Section: Strategies To Increase the Abundance Of A Muciniphilamentioning
confidence: 96%
“…An automatic preparation method for enriching microbiota from feces has been developed and is being used in serial FMT centers in China since 2014 (Cui et al, 2015;Cui et al, 2016;Qi et al, 2018;Wang et al, 2018;Ding et al, 2019;Huang et al, 2019). This method, originally designed on the concept of washed microbiota preparation is based on the automatic microfiltration machine (GenFMTer, Nanjing, China) and the following repeated centrifugation plus suspension with support from specific facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) has shown the therapeutic potential in many microbiota-related diseases beyond Clostridium difficile infection (CDI) [1,2], such as inflammatory bowel disease (IBD) [3][4][5][6][7], serious antibiotics-associated diarrhea in intensive care unit [8], irritable bowel syndrome (IBS) [9,10], constipation [11], primary sclerosing cholangitis (PSC) [12] and immune checkpoint inhibitor-associated colitis [13]. Methods of FMT delivery are classified into three routes: the upper gut, the mid-gut and the lower gut [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Then, in order to meet the needs of patients with multiple fresh FMTs or whole colon administration of drugs during a period of time, we developed a colonic delivery method by the long-term maintenance of an indwelling, colonoscopically placed transanal enteral tube, which was coined colonic TET [14]. The technique of placing a tube through the anus into cecum for whole colon administration of FMTs or medications is therefore achieved, and it has been successfully used in many hospitals in Asia in recent 2 years [6,10,14,24,25].…”
Section: Introductionmentioning
confidence: 99%